Novel Aromatic Polyamides from Bis-[p/m-(Aminobenzoylhydrazino)] Phosphite. - G.H. ZAIDI, MOHD.; SHUKLA, J.S.; DIXIT, S.K. (Asian Journal of Chemistry, 2010)
A series of aromatic polyamides from bis-[p/m-(aminobenzoylhydrazino)] phosphite with N-[p/m-(carboxyphenyl) ]aminoacetyl chloride have been synthesized in N,N-dimethylacetamide at -10oC and characterized by elemental and IR spectral analysis. The inherent viscosity of all polyamides measured at a concentration of 0.5 g dL -1 in m-cresol at 25± 1°C was found to be in the range of 0.09-0.29 dLg-1. Oxidative isothermal weight loss analyses have shown that all the polyamides were stable up to 300°C.